Rights of the conceived child - Gutiérrez Ramos, Miguel (2022)
Fertilization consists of the fusion of the male and female gametes in the outer thirdof the uterine tube to form the zygote, which begins its cell division, travels to theuterus, implants as a blastocyst in the endometrium after seven days and begins theprocesses of embryogenesis and morphogenesis. Conception is the action or effectof a woman becoming pregnant. About the rights established for the conceived, thebeginning of human life raises a wide discussion between the definitions proposedby science and those of civil society groups. Not being the zygote a human person,according to the Inter-American Court of Human Rights (IACHR) and others, it wouldnot be subject to the rights established for the person, which would be closelyrelated to the rights of the pregnant woman. Conception would occur when theembryo implants in the uterus and Article 4 of the IACHR would not apply. Peruviandoctrine, legislation and jurisprudence establish broad legal protection in favor ofthe conceived and indicate the beginning of life from the moment of fertilization.The Judgment of the IACHR in the case of Artavia Murillo v. Costa Rica introduces theSpanish figure of the pre-embryo, which is not granted legal protection until 14 days,when medical science establishes the implantation of the embryo in the maternalendometrium. For current ethical considerations, human pregnancy begins withthe implantation of the blastocyst in the endometrium and there is no basis foraccepting the right of the conceived from the moment of fertilization as if it were aperson. However, it is pointed out that human life has an uninterrupted continuityfrom conception to its natural end, death. The zygote is life that begins with its owngenetic endowment different from that of its progenitors. The preimplantationembryo can only give rise to a human being that is gestated and develops within thebody of another person, with its own vital dynamics.